The Role of Myeloid Cells on the Development of Hepatic Metastases in Gastrointestinal Cancer - Austin R. Dosch; Mary P. Martos; Samara Singh; Karishma Kodia; Nipun B. Merchant; Nagaraj S. Nagathihalli (Gastro Hep Advances)
The development of hepatic metastases is the leading cause of mortality in gastrointestinal (GI) cancers and substantial research efforts have been focused on elucidating the intricate mechanisms by which tumor cells successfully migrate to, invade, and ultimately colonize the liver parenchyma. Recent evidence has shown that perturbations in myeloid biology occur early in cancer development, characterized by the initial expansion of specific innate immune populations that promote tumor growth and facilitate metastases. This review summarizes the pathophysiology underlying the proliferation of myeloid cells that occurs with incipient neoplasia and explores the role of innate immune-host interactions, specifically granulocytes and neutrophil extracellular traps, in promoting hepatic colonization by tumor cells through the formation of the “premetastatic niche”. We further summarize the role of additional myeloid subpopulations such as monocytes and macrophages, dendritic cells, platelets, and eosinophils on promoting disease metastases in GI cancers. Lastly, we describe burgeoning therapeutic approaches aimed at targeting specific myeloid populations to reduce liver metastases and highlight the inherent challenges that exist in studying the efficacy of these treatments in preclinical models. As the inception and outgrowth of liver metastases are primary drivers of prognosis in GI malignancies; further research into the complex mechanisms involved in this critical process is urgently needed.